2012
DOI: 10.1007/s11606-012-2168-4
|View full text |Cite
|
Sign up to set email alerts
|

Medication Reconciliation Accuracy and Patient Understanding of Intended Medication Changes on Hospital Discharge

Abstract: BACKGROUND: Adverse drug events after hospital discharge are common and often serious. These events may result from provider errors or patient misunderstanding. OBJECTIVE: To determine the prevalence of medication reconciliation errors and patient misunderstanding of discharge medications. DESIGN: Prospective cohort study SUBJECTS: Patients over 64 years of age admitted with heart failure, acute coronary syndrome or pneumonia and discharged to home. MAIN MEASURES:We assessed medication reconciliation accuracy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 31 publications
3
88
1
Order By: Relevance
“…Many of these medical errors and adverse events are potentially preventable by improving communication between hospital staff, patients, and caregivers. Studies indicate that patients are routinely discharged with test results pending; unresolved plans for follow-up tests, appointments, or both; vague discharge orders; and insufficient contact with their physicians ( Ziaeian, Araujo, Van Ness, & Horwitz, 2012). This lack of communication and coordination results in patients being uninformed or misinformed about their illnesses or medications, lacking follow-up resources, and being not fully prepared to manage their own health ( Lum, Studenski, Degenholtz, & Hardy, 2012).…”
mentioning
confidence: 99%
“…Many of these medical errors and adverse events are potentially preventable by improving communication between hospital staff, patients, and caregivers. Studies indicate that patients are routinely discharged with test results pending; unresolved plans for follow-up tests, appointments, or both; vague discharge orders; and insufficient contact with their physicians ( Ziaeian, Araujo, Van Ness, & Horwitz, 2012). This lack of communication and coordination results in patients being uninformed or misinformed about their illnesses or medications, lacking follow-up resources, and being not fully prepared to manage their own health ( Lum, Studenski, Degenholtz, & Hardy, 2012).…”
mentioning
confidence: 99%
“…21 Other studies have found that patients' perceptions of understanding their discharge instructions, including medications, do not indicate actual understanding in the older adult population. 22,23 Ziaeian et al 22 found that by interviewing patients aged 64 and over and asking them to name their medications, misunderstanding about medication changes, such as dose changes, new medications, and stopping medications, occurred as often as 88.7% of the time. Despite patients' perceptions of understanding each of their medications well, as observed in the present study, these perceptions may not accurately reflect patients' understanding.…”
Section: Discussionmentioning
confidence: 99%
“…23) Pharmacists can be helpful as a resource for medication reconciliation. 24,25) The process also provides an opportunity for clinicians to ensure that patients understand which medications they are consuming, how to consume them, and why they are consuming them. [26][27][28][29][30] From this study, the importance of care for cognitive function and excretion in home care is clarified.…”
Section: Discussionmentioning
confidence: 99%